A Case of the Intrapulmonary Spread of Recurrent Respiratory Papillomatosis With Malignant Transformation. (July 2015) - Xiao, Yang; Wang, Jun; Han, Demin; Ma, Lijing
Abstract: Objectives: To describe an individual with recurrent respiratory papillomatosis that extended into the lung parenchyma and underwent malignant transformation and to discuss the characteristic imaging findings associated with this condition. Methods: The clinical presentation of an individual with this unusual malignant transformation was reviewed. A literature search was performed to characterize the epidemiology, imaging findings and management of this condition. Results: The patient underwent 30 courses of surgery over 21 years and presented disseminated pulmonary papilloma after childbirth. The interval between dissemination into the lung and malignant transformation was 2.5 years. The tracheal papilloma was positive for type 6 of human papilloma virus (HPV-6). She died because she refused further treatment. Conclusions: The clinician should have a high index of suspicion for lung papillomatosis in patients with a tracheotomy. Appropriate diagnostic imaging studies will be helpful in reaching this diagnosis and determining whether a malignancy exists. Treatment options have limited success when lung papillomatosis becomes malignant.